Pengaruh Media Sosial Facebook Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam” Pada Siswa SMAN 10 Kabupaten Tangerang - As’ari; Desty Endrawati Subroto; Mohamad Bayi Tabrani (Concept: Journal of Social Humanities and Education, 2023)
Quantitative descriptive research is a type of non-experimental quantitative research that is relatively easy. This study describes the quantitative data obtained concerning the condition of the subject or phenomenon of a population. The research instrument that is often used in this study is a questionnaire containing several question items about perceptions of research problems. The results of testing the alternative hypothesis proposed are significantly acceptable, namely, with a positive influence between the Effect of Facebook Social Media on Concentration and Learning Outcomes at SMAN 10.The results of the analysis on the coefficients show that the value of the correlation coefficient indicates that the rxy coefficient value is 0.751, so it is stated in the strong category, and the rtable is 0.306. rcount > rtable = 0.751 > 0.306, and the results of the t test obtained the price of tcount of 6.026 while ttable of 1.69726 with an error rate of 5%, thus tcount > ttable = 6.026 > 1.69726, it can be concluded that the correlation coefficient between Social Media Facebook and Concentration and Learning Outcomes have a positive and significant effect and from the hypothesis testing that has been done Ho is rejected and Ha is accepted, and the coefficient of determination (cd) is 56%, based on the relationship between these variables is causal or causal, a simple linear regression equation can be made, namely Y = a + bX, a = 28,941, while the value of b is b = 0.650 X. Then a simple linear regression equation can be obtained, namely Y = 28,941 + 0,650 X so that there is the influence of Facebook social media on concentration and learning outcomes at SMAN 10 Tangerang Regency.